Conocimientos tradicionales de los pobladores en la adaptación y resiliencia de los sistemas agroforestales en Cañaveral y San Miguel, Río Amazonas, Loreto, 2025 - Perez Perez, Luis Javier (2025)
This quantitative, descriptive, non-experimental, cross-sectional study aimed to analyze the contribution of traditional knowledge to the adaptation and resilience of agroforestry systems to flooding and its impact on food security in the riverine communities of Cañaveral and San Miguel, located on the Amazon River in Loreto. The sample consisted of 30 families from Cañaveral and 12 from San Miguel, selected through convenience sampling and census-based methods. A structured 7-item survey was administered, whose reliability was validated using Cronbach's alpha coefficient (α = 0.715). Descriptive and inferential analysis included the Shapiro-Wilk normality test and Spearman's correlation coefficient. The results showed the existence of ancestral practices such as species selection and agricultural diversification, although with limited application of specific techniques in response to intense flooding. It was found that residents who preserve and apply more traditional knowledge have higher levels of resilience and improved food security. However, limitations such as the loss of intergenerational knowledge, limited technical assistance, and external pressures such as deforestation persist. Significant differences were observed between the two communities: in Cañaveral, a strong correlation between traditional knowledge and resilience was found, while in San Miguel, this relationship was weak and nonsignificant. These findings reflect the crucial role of ancestral knowledge in agroforestry sustainability in the face of hydrometeorological events.